Effect of Applying Leadership and Strategic PlanningAccording to the International Standard ISO 9001-2015 for strategic success: Effect of Applying Leadership and Strategic PlanningAccording to the International Standard ISO 9001-2015 for strategic success - Abbood, Imran (The Gulf Economist, 2023)
This research aims to measure the impact of applying the requirements of leadership and strategic planning according to the international standard (ISO9001:2015) on the strategic success of the Arabian Gulf Academy for Maritime Studies by referring to a statement of weaknesses and strengths related to the application of these items and studying their impact on increasing levels of strategic success for the mentioned research sample. The researcher adopted a survey methodology by collecting data and information from personal interviews and by developing a questionnaire to ensure relationship between the two variables of the study, i.e., the independent and dependent ones. A Survey for the opinions of (180 individuals), represented by the senior and middle management staff of Arabian Gulf Academy of Maritime Studies, were surveyed. The researcher relied on the statistical programs SPSS.V24 and AMOS.V.24 in analyzing the questionnaire data. The results of the statistical analysis concluded that there is an effect between the dimensions of the international standard represented by the two items, i.e., leadership and strategic planning, each as a separate and combined. The dimensions of the strategic success variable and the strategic success variable also analyzed in total. The study concluded number of recommendations, the most important of which is the need to make adjustments and changes in the quality management system applied in the Academy in line with achieving the best compatibility with the international quality management system. This will allow it to achieve strategic success, and increase the confidence and sincerity of the parties concerned, and emphasizing the implementation of all dimensions of strategic success to raise the organization to the required level.